2017
DOI: 10.1590/1678-77572016-0306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different composite core materials on fracture resistance of endodontically treated teeth restored with FRC posts

Abstract: Objective This study evaluated the fracture resistance of endodontically treated teeth restored with fiber reinforced composite posts, using three resin composite core build-up materials, (Clearfil Photo Core (CPC), MultiCore Flow (MCF), and LuxaCore Z-Dual (LCZ)), and a nanohybrid composite, (Tetric N-Ceram (TNC)).Material and Methods Forty endodontically treated lower first premolars were restored with quartz fiber posts (D.T. Light-Post) cemented with resin cement (Panavia F2.0). Samples were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…This may be due to the fact that amalgam materials are still not considered as a health threat to the patient and have a good level of acceptability. In addition, resin-based composite core materials are more popular due to their chemical bond to the tooth structure and similarity to the tooth structure in terms of hardness and fracture toughness, offering the advantage that preparation can be performed after curing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that amalgam materials are still not considered as a health threat to the patient and have a good level of acceptability. In addition, resin-based composite core materials are more popular due to their chemical bond to the tooth structure and similarity to the tooth structure in terms of hardness and fracture toughness, offering the advantage that preparation can be performed after curing [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…, Rödig et al . , Panitiwat & Salimee ). However, from a research perspective, it is important to note that the increased percentage of filler in these materials needed for core build‐up leads irreversibly to higher stress during polymerization, ultimately resulting in lower bond strength values (Ferrari et al .…”
Section: Restoration Conceptsmentioning
confidence: 99%
“…These findings could be referred to the favorable biomechanical properties of fiber posts and composite cores. [ 29 30 ] Giovani et al [ 31 ] utilized the same concept to explain his supporting results. They reported that glass fiber posts with modulus of elasticity similar to dentin can absorb the stresses better, reducing the probability of catastrophic root fracture accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…This feature can accordingly result in core failure in cases utilizing composite cores, while those utilizing cast post-core usually show root fracture. [ 26 29 40 ]…”
Section: Discussionmentioning
confidence: 99%